Developing a policy for Mangosuthu Technikon as a case study on HIV and Aids and the challenges in policy development and implementation of HIV and Aids programmes and education - Sithole, Thembinkosi Berresford (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2005.